Association of HIVEP3 Gene and Lnc RNA with Femoral Neck Bone Mineral Content and Hip Geometry by Genome-Wide Association Analysis in Chinese People - Zhang, Zhenlin; Wang, Yi; Gu, Jiemei; Yue, Hua; Wang, Chun; Qi, Luyue; He, Jinwei; Hu, Weiwei; Zhang, Hao (International journal of endocrinology, 2020)
Purpose. GWAS has successfully located and analyzed the pathogenic genes of osteoporosis. Genetic studies have found that heritability of BMD is 50%–85% while the other half is caused by hip geometric parameters and tissue horizontal characteristics. This study was designed to study the GWAS of osteoporosis in Shanghai Han population. Methods. We collected 1224 unrelated healthy young men (20–40 years old), young women (20–40 years old), and postmenopausal women (over 50 years old) who lived in Shanghai. BMD and hip geometric parameters were measured by dual-energy X-ray absorptiometry. The genomic DNA of peripheral blood was extracted and analyzed by using Illumina Human Asian Screening Array-24 + v1.0 (ASA) gene chip. Statistical analysis was carried out to evaluate the relationship between these SNPs and BMD and hip geometric parameters. Results. A total of 1155 subjects were included. We found that one SNP rs35282355 located in the human immunodeficiency virus type 1 enhancer-binding protein 3 gene (HIVEP3) and another 25 SNPs located in LINC RNA were significantly correlated with bone mineral content (BMC) in the femoral neck (P= 2.30 × 10−9, P < 5 × 10−8). We also found that the correlation between SNP rs35282355 and cross-sectional area (CSA) of hip geometry was a significant marginal statistical difference (P = 5.95 × 10−8). Conclusions. Through this study, we found that HIVEP3 gene and LINC RNA are potentially correlated with femoral neck BMC. These results provide important information for us to further understand the etiology and genetic pathogenesis of osteoporosis. In the future, we will expand the sample size to verify these loci and carry out molecular research.